The Current State of the Vertebrate Animals Populations and their Role in the Persistence of Natural Zoonoses Foci in the Stavropol Territory - N. F. Vasilenko; D. A. Prislegina; N. V. Tsapko; A. S. Volynkina; O. V. Semenko; U. M. Ashibokov; Yu. M. Tokhov; O. V. Maletskaya; A. N. Kulichenko (Проблемы особо опасных инфекций, 2022)
The aim of this study was to investigate the current state of vertebrates populations and to determine their role in maintaining natural foci of zoonoses in the Stavropol Territory in 2015–2019. Material and methods. Organ suspensions and blood samples from small mammals and birds were studied using certified diagnostic test-systems for the markers of Crimean hemorrhagic fever, West Nile fever, hemorrhagic fever with renal syndrome, tularemia, and leptospirosis pathogens. The data were statistically processed using Wilson’s method. Results and discussion. Identified have been the main reservoirs of natural-focal infections in the Stavropol Territory at the present stage: birds – for the West Nile fever virus, mammals and birds inhabiting the areas of semi-desert landscape-geographical zone – for Crimean hemorrhagic fever agent. The main natural reservoir of orthohantaviruses in the Stavropol Territory is the common vole Microtus arvalis, which lives in all landscape-geographical zones. The circulation of tularemia and leptospirosis pathogens has been established throughout the whole territory of the region, the small wood mouse Sylvaemus uralensis is of the greatest epizootic significance. Findings indicate the need for further epizootiologic monitoring of Stavropol Territory in order to identify the biocenotic patterns of the pathogens’ existence and the reasons that determine the dynamics of the epizootic process and epidemic manifestations of natural foci. It is advisable to determine the sites of long-term monitoring over the number of carriers and vectors of natural-focal infections and strengthen the epizootiological control over the territory, especially during periods of seasonal activity in carriers and vectors of natural focal infections.